Rancang Bangun Panel Listrik 3 Phase Untuk Kegiatan Praktikum Di Laboratorium Instalasi Listrik - Kussoy, Steven Daniel; Prasetyo, Julyar; Widodo, Slamet (JST (Jurnal Sains Terapan), 2024)
The Electrical Installation Laboratory of the Electrical Engineering Department of the Balikpapan State Polytechnic does not yet have a 3 phase electrical installation and panels for practicums that use a 3 phase electric motor power circuit in order to install and assemble the power circuit. Vocational-based higher education that provides knowledge of industrial machines to students of the Electronics Engineering Study Program and electric motor electricity to students of the Electrical Technology Study Program is very important for getting to know, deepening and practicing knowledge about 3 phase electricity and 3 phase electric motor circuits for industrial automation purposes because of the material This knowledge really exists and is required to be known in the industrial world. A 3 phase electrical panel is a device that functions to divide, channel and distribute electrical power from an electricity source/center to consumers/users, especially electrical installation laboratories that serve education, research and community service. The aim of this research is to build a 3 phase electrical panel in the Electrical Installation Laboratory so that students can practice using 3 phase electrical voltage. This research method is an experimental method, consisting of 4 stages, namely starting with literature study, designing and making tools, testing tools and collecting data and finally the tool implementation stage. The test results in this research show that the voltage output from the MCCB has produced an average voltage of 380V for 3 phase voltage and 220V for 1 phase voltage, and is in accordance with PUIL 2011 standards so that the voltage distributed from the MCCB is safe and ready to be used to be transmitted to the socket. 3 phases. This research will be very useful in developing electrical installation laboratories and applied technology in the field of electronics and electricity. Keywords : 3 phase electricity, installation, electrical panels, electric motors, electronics and electricityLaboratorium Instalasi Listrik Jurusan Rekayasa Elektro Politeknik Negeri Balikpapan belum memiliki instalasi listrik 3 phase dan panelnya untuk praktikum yang menggunakan rangkaian daya motor  listrik 3 phase agar dapat memasang dan merakit  rangkaian daya. Pendidikan tinggi berbasis vokasi yang memberikan ilmu mesin industri kepada mahasiswa Program Studi Teknik Elektronika dan kelistrikan motor listrik kepada mahasiswa Program Studi Teknologi Listrik sangat penting untuk mengenal, memperdalam dan mempraktikkan ilmu mengenai listrik 3 phase dan rangkaian motor listrik 3 phase untuk tujuan otomasi industri karena materi ilmu tersebut sangat ada dan dituntut untuk tahu di dunia industri. Panel listrik 3 phase adalah sebuah perangkat yang berfungsi membagi, menyalurkan dan mendistribusikan tenaga listrik dari sumber/pusat listrik kekonsumen/pemakai khususnya laboratorium instalasi listrik yang melayani pendidikan, penelitian, dan pengabdian kepada masyarakat. Tujuan Penelitian ini adalah membangun panel listrik 3 phase di Laboratorium Instalasi Listrik sehingga mahasiswa dapat praktik menggunakan tegangan listrik 3 phase. Metode penelitian ini adalah metode eksperimental, terdiri dari  4 tahapan yaitu diawali dengan studi literatur, perancangan dan pembuatan alat, pengujian alat dan pengambilan data serta terakhir tahap implementasi alat. Hasil pengujian pada penelitian ini menunjukkan bahwa keluaran tegangan dari MCCB sudah menghasilkan tegangan rata-rata 380V untuk tegangan 3 phase dan 220V untuk tegangan 1 phase, serta sesuai standar PUIL 2011 sehingga tegangan yang disalurkan dari MCCB sudah aman dan siap digunakan untuk diteruskan ke stop kontak 3 phase. Penelitian ini akan sangat bermanfaat dalam pengembangan laboratoratorium instalasi listrik dan ilmu teknologi terapan dalam bidang elektronika dan kelistrikan. Kata kunci :  listrik 3 phase, instalasi, panel listrik, motor listrik, elektronika dan kelistrikan